Kepala Sekolah Sebagai Administrator Terhadap Pengelolaan Administrasi: Studi Kasus di SDN 2 Sikur Selatan - Ari Suandi (PT. Nawa Edukasi Nusantara, 2025)
This study aims to determine the role of the principal as an administrator in managing administration and to determine the efforts made to improve administrative management. This study used qualitative, descriptive methods. Data collection was conducted through observation, interviews, and documentation. The sources of this study were the principal, administrative staff, and teachers. The results of this study indicate that the principal at Elementary school 2 Sikur Selatan has carried out his role as an administrator quite well. To determine how the principal carries out his role as an administrator, it can be seen from the implementation of administrative functions, namely planning, organizing, coordinating, directing, supervising, and evaluating. The next step in efforts to improve administrative management is to pay more attention to monitoring administrative activities to ensure they continue according to plan.